Serious games para a fonoaudiologia: uma abordagem voltada à terapia em motricidade orofacial - Sousa, Azuíla da Silva (2011)
Due to the development of computer technology and its presence in the daily routine of professionals and students, more resources have emerged with the aim of providing an efficient way to transmit and enhance knowledge in all fields of science. In medical and therapeutic offices, is commonplace to note the existence of computer tools such as visualization applications, games and simulators that enable therapeutic methods based on information technologies and communication. Due to the fact that Speech Pathology is a profession in constant development, this study proposes describing and demonstrating the importance of using technology in speech-language therapies. Thus, it was necessary to conduct a field survey for lifting the profile of professionals of speech pathology on the use of technology in their clinical practice as well as a literature search on existing applications in general healthcare and in speech therapy. Later, it was proposed the building of an application to support rehabilitation processes. It was noticed that there is need for research directed to the field of Speech-therapy concerning to the use of assistive technology for speech-language therapies. Although there are specific computer programs for rehabilitation, little is known about the evaluation and validation of these software in scientific literature. It was developed a game as a way to assist in the treatment of atypical swallowing. The game, called MOtrilha, can support therapeutic techniques for the correction of atypical swallowing. It is one more tool to help professionals and to motivate patients.